Protein and Hormone Profiling of Hormone-Treated or Untreated Excised Oil Palm (Elaeis Guineensis Jacq.) Spear Leaves - Mohamed Ramly, Halina (2010)
Clonal propagation of elite oil palm hybrids via tissue culture has been developed over the past twenty years, but still not perfect. In the procedure,an initial callus phase is required to establish primary cultures. However, the initiation and proliferation of callus in oil palm is a slow process with a low success rate ranging between 20 and 50%. Furthermore, the time required for the initiation and the percentage of callusing varies by genotype and origin of the palm materials. This setback may be attributed by the inappropriate combinations and levels of plant growth regulator (PGR) used in the media. This study was undertaken to evaluate the effect of clonal material and PGR concentration on callus induction, to determine the existance of exogenous hormones and also to determine the expression of proteins associated with toxicity levels of 2, 4-diclorophenoxyacetic acid (2,4-D) by SELDI-TOF profiling. Excised leaves of Tenera population were exposed exogenously to 2, 4-diclorophenoxyacetic acid (2, 4-D), benyladenine (BA) and kinetin (K) at 0, 0.1, 1.0, 2.5, 5.0, 10.0 and 15.0 mg/L concentrations, alone and in combinations. The range of 2,4-D concentrations for oil palm callus formation was between 0.1 mg/L and 2.5 mg/ as evaluated after 4 months of incubation. However, at high concentrations of 2,4-D i.e. 10 -15 mg/l, the explants turned brown and some were dried up. Morphological changes on these explants indicated that 2,4-D at 0.1 mg/L was the most appropriate for callus induction. Hormonal profiling was conducted to determine the existence of the hormones in the samples exposed exogenously to 2,4-D, BA and kinetin (K). The experiment revealed that 2,4-D was undetectable by HPLC, and very low amounts of BA and kinetin (K) were traced. In conjunction with the influence of hormone especially 2,4-D on callogensis and exogenous hormone profiling, the study has been extended to evaluate the influence of 2,4-D on protein expressions by using SELDI-TOF MS (Surface-Enhanced Laser Desorption/Ionization-Time of Flight Mass Spectrometry). Expressed proteins that are associated with toxicity levels of 2,4-D in oil palm spear leaves were profiled and analysed. A set of up-regulated and down-regulated proteins was expressed at different concentrations of 2,4-D with some were only present at 4.0 mg/L 2,4-D (15.94 kDa, 19.91 kDa, 20.8 kDa and 24.7 kDa). The presence of these proteins in cultured explants may reflect a specific biochemical event that appears in response to high or toxic concentrations of 2,4-D. Subject to further validation, these proteins may potentially be used as biochemical markers for indicating the suitability of 2,4-D concentrations in oil palm tissue culture media.